Pelatihan Dasar Kepemimpinan Publik dan Manajemen Program bagi Mahasiswa Calon Duta GenRe Kota Padang Panjang - Mardhatillah, Muntaha; Kahanna, Mutia (-, 2025)
This community service activity aims to improve the public leadership and program management capacity of students who are candidates for Generation Planning Ambassadors (GenRe) in Padang Panjang City. Students and pupils nominated as GenRe Ambassadors play a strategic role as agents of change in supporting population programs and youth development. However, this role requires structured and results-oriented leadership and program management skills, necessitating systematic training activities. The community service program was conducted using an educational and participatory approach via Zoom. The activity was attended by 30 participants from various universities and high schools in the province of West Sumatra. The activity included lectures on public leadership and program management, interactive discussions, and question-and-answer sessions. The activity was evaluated through a questionnaire filled out by participants to assess the relevance of the material, the implementation method, and the benefits of the activity. The results of the activity showed an increase in participants' understanding of the role of public leadership and basic program management skills. Participant evaluations showed ratings ranging from good to very good, especially in terms of the relevance of the material and the benefits of the activity. This indicates that online training remains effective in improving the capacity of prospective GenRe Ambassadors. This community service activity contributes to supporting the development of a competitive and integrity-driven young generation, as well as strengthening the synergy between universities, BKKBN, dan Dinas Sosial, Pengendalian Penduduk, Keluarga Berencana, Pemberdayaan Perempuan, dan Perlindungan Anak Kota Padang Panjang in strengthening the GenRe program at the local level